PENGARUH MODIFIKASI BACKCUT SEAT VALVE DAN UNDERCUTSTEM TERHADAP EFISIENSI VOLUMETRIK PADA CYLINDER HEAD MESIN ASTRO 108 CC - Aldi Prasetiyo; Sudarno sudarno; Yoga Arob Wicaksono (KOMPUTEK, 2021)
As technology develops in the automotive world, more and more motor vehicle manufacturers are also applying the latest technologies, especially for vehicles sold in general. Call it, for example, the development of the fuel system, which was still a carburetor, now uses an injection system, from S.O.H.C to D.O.H.C. these technologies are useful for increasing volumetric efficiency. In this study, the researchers wanted to increase the volumetric efficiency of the Astro 108 cc engine by applying a simple modification, namely the inlet and exhaust that was modified with a 30 backcut on the valve, undercut system, and 4 angle valve jobs (30 , 45, 60 , 75 ). By applying these modifications to the Astro 108 cc engine, it can increase its volumetric efficiency, say at 2300 rpm with standard inlet and exhaust conditions producing an air flow rate of 0.000358 m3 / s and 0.000814 m3 / s, this data is obtained from pressure taking on the water box meter. The difference in flow occurs because the air that enters the inlet and exhaust is smoother due to the modifications made. With this flow rate, at 2300 rpm standard head produces a volumetric efficiency of 19.05712%, and 43.26364% with a modified head.